PANTALLAS TÁCTILES Y SU INCIDENCIA EN LOS PROCESOS DE ENSEÑANZA-APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE EDUCACIÓN BÁSICA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO OCTUBRE 2023 – MARZO 2024. - CANDELARIO VILLAMAR ANA MARIA (2024)
The main objective of this research work is to determine the incidence of touch screens in the teaching-learning process in students of the Basic Education program at the Technical University of Babahoyo, since this technological tool has the potential to promote the acquisition of significant learning in the student body, and satisfactorily complement the teaching provided by the teacher, based on the different syllabi planned from the beginning of the academic period. The methodology used in the research was two types: descriptive and exploratory, the deductive method was used, since it allowed us to go from the general to the specific and concrete that contributed to the conclusions; Information was collected from reliable sources that complemented the theoretical support, with the use of the quantitative approach, the tabulation of data provided by the sample was carried out through the survey that provided relevant and conclusive information, it consisted of 12 closed questions addressed to both the 20 teachers Like the 243 students who received the sampling formula, it was applied through Google Forms. Based on all the procedures correctly applied, the objectives set in the research were met, leading to the ratification of the positive adaptation of these new technologies in the classroom of the aforementioned individuals. Finally, based on the results obtained in the research, it was evident that the implementation of touch screens provides various benefits, also developing skills and abilities